2021
DOI: 10.1186/s12889-021-11069-0
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel mixed effects analysis of individual and community level factors associated with modern contraceptive use among married women in Uganda

Abstract: Background In spite of the universal right for women to decide freely for themselves when, and how many children they want to have in life, married women in Uganda are less likely to use modern contraceptives as compared to other marital categories. This study examines the individual and community factors associated with modern contraceptive use among married women in Uganda. Methods The study used data from the 2016 Uganda Demographic and Health S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
4
6
0
1
Order By: Relevance
“…Economic status was found to have a relationship with contraceptive use in all regions except Kalimantan and the Maluku Islands. This nding is in line with a study by Wasswa, Kabagenyi, and Ariho [37], which found that middle-or upper-class women have a higher chance of using modern contraception than women in the lower class. Such a difference is because women from wealthy households may have better access to modern contraceptives than women from low-income families.…”
Section: Discussionsupporting
confidence: 91%
“…Economic status was found to have a relationship with contraceptive use in all regions except Kalimantan and the Maluku Islands. This nding is in line with a study by Wasswa, Kabagenyi, and Ariho [37], which found that middle-or upper-class women have a higher chance of using modern contraception than women in the lower class. Such a difference is because women from wealthy households may have better access to modern contraceptives than women from low-income families.…”
Section: Discussionsupporting
confidence: 91%
“…This outcome is similar to the results of studies conducted in Uganda. 36 This is logical because these mothers did not give birth in the age range, they were supposed to give birth to, and they were now too old to try to have a baby before they stopped giving birth. Consequently, women at the ¥ 20 years were more likely to use contraceptives.…”
Section: Discussionmentioning
confidence: 99%
“…Program pemerintah harus melakukan inovasi. Nagari itu dari penyetaraan gender karena di sisi ekonomi kebanyakan dari data yang ada, angka kemiskinan berada pada perempuan (Shai et al, 2021;Wasswa et al, 2021). Fokus perhatian penelitian ini adalah wacana kepemimpinan perempuan, bagaimana perempuan ditampilkan dalam tuturan sebagai pihak yang lemah, marjinal dibanding dengan pihak lakilaki.…”
Section: Pendahuluanunclassified